2015
DOI: 10.11648/j.ajbls.20150306.13
|View full text |Cite
|
Sign up to set email alerts
|

Production Optimization and Characterization of Amylase Enzyme Isolated from Termofil Bacteria <i>Bacillus sp</i> RSAII-1b from Lejja Hot Spring South Sulawesi

Abstract: Thermostable amylase enzyme has a broad commercial value in its use in the processing of starch, sugar production, textile, paper, animal feed, pharmaceuticals and in the manufacture of detergents. This study aims to determine the optimum conditions of amylase production from the termofil bacteria Bacillus sp. RSII-1b isolated from a hot spring Lejja South Sulawesi and characterizing the amylase enzyme. The testing of amylase production was done with various concentration of starch and CaCl 2 in the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The maximum enzyme activity (80.6 U/mL/min) was accomplished when the bacterial strain was grown at a temperature at 54.1°C. This agreed with Arfah et al [ 33 ] and Tiwari et al . [ 34 ] who reported that the optimum temperature of amylase production was at 55°C by Bacillus sp.…”
Section: Discussionsupporting
confidence: 93%
“…The maximum enzyme activity (80.6 U/mL/min) was accomplished when the bacterial strain was grown at a temperature at 54.1°C. This agreed with Arfah et al [ 33 ] and Tiwari et al . [ 34 ] who reported that the optimum temperature of amylase production was at 55°C by Bacillus sp.…”
Section: Discussionsupporting
confidence: 93%
“…Due to its location in the Pacific ring of fire, Indonesia provides a rich ecosystem at hot spring sites where numerous thermophilic bacteria species can thrive successfully. A few of these bacterial isolates were reported to produce thermostable industrial enzymes such as amylase, lipase, protease, and xylanase [15][16][17]. Interestingly most of the isolates that have been isolated from the Cangar hot spring, the current study site, are identified as members of genus Bacillus, which predominantly includes Bacillus licheniformis strains [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in enzyme activity in each isolate is caused by the amount and activity of the enzyme secreted from each isolate (Agustien, 2005). Screening and testing for amylase activity were also conducted by Arfah et al, (2015) who obtained R-SAII-1b isolates from hot springs Lejja (South Sulawesi) with an activity of 0.0711 U/mg protein.…”
Section: Production and Amylase Activitymentioning
confidence: 99%